PENGARUH PERSEPSI ETIS DAN RELIGIUSITAS TERHADAP NIAT UMKM MELAKUKAN PINJAMAN ONLINE PADA MASA COVID-19 - Dewi Kusuma Wardani; Simon Pulung Nugroho; Adia Adi Prabowo (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2021)
The high of the online loan platforms growth is a solution for MSME to raising fund during the Covid-19 pandemic. However, online loans are known have unethical business process and violate religious value. This study was conducted to capture whether a persons ethical and religious perceptions can reduce the intention to make an online loan. This study uses questionnaires to collect data and snowball sampling method to get sample. This study uses multiple regression analysis to analize the data. This study found two results. First, ethical perceptions can reduce the intention to make online loans. Second, religiousity has no effect on intention to make online loans. The implication of this research is that borrowers use their ethical perception to reduce ther intention to make online loans rather than their religious values. Therefore, online loans platforms should increase ethical value in their business processes by not charging too high interest and more humane collection process.